Batch and Fed-Batch Fermentation System on Ethanol Production from Whey using Kluyveromyces marxianus - Hadiyanto, H; Ariyanti, D.; Aini, A.P.; Pinundi, D.S. (International Journal of Renewable Energy Development, 2013)
Nowadays reserve of fossil fuel has gradually depleted. This condition forces many researchers to  find energy alternatives which is renewable and sustainable in the future. Ethanol derived from cheese industrial waste (whey) using fermentation process can be a new perspective in order to secure both energy and environment. The aim of this study was  to compare the operation modes (batch and fed-batch) of fermentation system on ethanol production from whey using Kluyveromyces marxianus. The result showed that the fermentation process for ethanol production by fed-batch system was higher at some point of parameters compared with batch system. Growth rate and ethanol yield (YP/S) of fed-batch fermentation were 0.122/h and 0.21 gP/gS respectively; growth rate and ethanol yield (YP/S) of batch fermentation were 0.107/h, and 0.12 g ethanol/g substrate, respectively. Based on the data of biomass and ethanol concentrations, the fermentation process for ethanol production by fed-batch system were higher at some point of parameters compared to batch system. Periodic substrate addition performed on fed-batch system leads the yeast growth in low substrate concentrations and consequently  increasing their activity and ethanol productivity.